2017
DOI: 10.1177/1350650117723484
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing characteristics of high-speed spindle bearing under constant preload

Abstract: Bearings play an important role in a high-speed spindle. Its characteristics are often influenced by speed and thermal effects. This paper presents an approach that combines an inverse method with a high-speed ball bearing model to determine the characteristics of a high-speed spindle bearing under constant preload in actual working conditions. With temperature distribution in the entire spindle obtained by the experimental inverse heat transfer model from the authors’ previous results, the change in bearing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As shown in Fig. 6 [39], when rotation speed reaches 10,000 r/min, contact stress of inner ring ( Fig. 6a) is 958.2 N/mm while the outer ring ( Fig.…”
Section: Fatigue Life Based Criterionmentioning
confidence: 85%
See 2 more Smart Citations
“…As shown in Fig. 6 [39], when rotation speed reaches 10,000 r/min, contact stress of inner ring ( Fig. 6a) is 958.2 N/mm while the outer ring ( Fig.…”
Section: Fatigue Life Based Criterionmentioning
confidence: 85%
“…The critical speed increase along with the preload rise, while the spindle vibration has a contrary trend, however the decrease tends to slowly when the preload reaches a certain extent [117,118]. Ngo [39] studied the spindle properties in terms of preload from the perspective of oil film thickness variation. Matsubara [119] analyzed the interactions among stiffness, temperature rise and natural frequency of HSS by non-contact loading method, indicated the natural frequency increased with temperature rise and then decreased after temperature reached stable.…”
Section: Comprehensive Influence Of Uniform Preload On Spindle Dynamimentioning
confidence: 99%
See 1 more Smart Citation
“…To carry out the deformation of bearing, solving a quasi-static model for high speed ball bearing must be performed. Based on the Matlab code developed by Ngo et al., 29 the quasi-static of present bearing is worked out to obtain speed-dependent δa for several preloads as displayed in Figure 12. It is observed that value of δa nonlinearly increases with increasing the spindle speed.…”
Section: Thermal Model Developmentmentioning
confidence: 99%
“…Tan et al [18] proposed an alternative assisted differential evolution method to obtain more accurate convective heat transfer coefficients in finite element thermal analysis of spindles. Ngo et al [19] obtained the spindle temperature distribution using an experimental inverse heat transfer model and determined changes in bearing characteristics by replacing varying parameters in the model. Zhou [20] et al introduced a distributed measurement method based on fiber Bragg grating for multi-point measurement of inner and outer ring temperatures in bearings to study their thermal behavior and distribution patterns.…”
Section: Introductionmentioning
confidence: 99%